A Subcategorization of Tagalog Verbs - Cruz, Emilita L. (The Archive; Vol 2 (1975): Special Monograph Issue No. 2: A Subcategorization of Tagalog Verbs, 1975)
This study of Tagalog verbs is a slightly revised version of a masteral thesis submitted in 1971 to the Department of Linguistics and Asian Languages, College of Arts and Sciences, University of the Philippines. It follows and integrates two masteral theses both submitted earlier in 1962 to the same department. The fist of the two theses is Antonia C. Silverio’s “The Passive Verbal Constructions in Tagalog” in which Tagalog verb stems are classified on the basis of the passive affixes which can cooccur with them. The second thesis is Lydia Fer. Gonzales’s “The Active Sentences and Active Verbs in Tagalog” in which Tagalog verb stems are classified on the basis of the active affixes and complements which can cooccur with them. The present study classifies Tagalog verb stems on the basis of both the active and passive affixes as well as the complements which can cooccur with them. We hope that the publication of this study will stimulate further studies on the verbs of Tagalog and other Philippine languages.